Cancer Bioinformatics - Kais, Ghedira; Hamdi, Yosr (Biomedical Engineering, 2022)
This book discusses the application of bioinformatics in cancer disease management. It covers general aspects of cancer as a disease but also as a success story in the translation of omics data in clinical settings. It provides an overview of the specific applications of bioinformatics tools in cancer epidemiology, prevention, and screening and in the identification of novel genetic and molecular biomarkers involved in cancer development. This is accomplished through the inclusion of numerous examples of the use of bioinformatics in precision oncology.